Transitioning out of illegalization: Cross-border mobility experiences - Consoli, Liala; Burton-Jeangros, Claudine; Jackson, Yves (Frontiers in Human Dynamics, 2022)
It is known that opportunities to cross borders legally, acquired through regularization programs, are acknowledged by previously illegalized migrants as one of the main positive effects of obtaining a residence permit. However, the impact of these policies has rarely been investigated through the ‘mobility lens’. To fulfill this gap, this study aims, through a case study, 1) to assess how obtaining a residence permit after having endured years of illegalization affects migrants’ cross-border mobility and 2) to identify the direct and indirect transformative effects triggered by these changes in cross-border mobility. Our analysis considers regularization policies as a transformation of mobility regimes in which individual mobility trajectories are embedded. Thirty-nine migrants transitioning out of illegalization through an extraordinary regularization program implemented between 2017 and 2018 in the Canton of Geneva, Switzerland, were interviewed twice at a time interval of more than 1.5 years. Changes in actual mobility and perceived potential mobility (‘motility’) were identified in the narratives. Inductive thematic analysis was used to identify related transformative effects. As a complement, descriptive statistics using two-wave panel data collected among a broader sample of migrants in the same context provided quantitative measures of cross-border mobility. Our findings highlight the importance of considering changes related to cross-border mobility when studying the impact of regularization programs on migrants’ well-being, as they are a crucial ingredient of deeper adjustments occurring in their lives. We emphasize the importance of considering not only the subjective and objective effects triggered by increased actual mobility but also the subjective effects triggered by perceived increased potential mobility. Indeed, becoming aware of the new opportunities to cross borders leads to transforming imagined futures, subjectivities, identities, concerns, and perceived sources of stress, and affects emotional well-being. The findings underline the relevance of a processual approach for two reasons: first, having experienced a long-lasting illegalization and forced immobility continues to affect individuals’ experience of cross-border (im)mobility even after regularization; second, the triggered transformative effects take time to develop and observations at different times give a richer picture.